INTERBREED AND INTRABREED VARIABILITY IN RABBITS AND ITS ROLE IN BREEDING - N. A. Balakirev; R. M. Nigmatullin (Вавиловский журнал генетики и селекции)
Interbreed and intrabreed variability in basic measurements and body indices was studied in rabbits of the eight most widespread breeds. Three blockiness types were recognized: narrow-bodied, intermediate, and wide-bodied. The White Giant, Black Brown, and Gray Giant breeds belonged to the narrow-bodied type; Viennese Blue, Silvery, and Soviet Chinchilla, to intermediate; and Californian and New Zealand White, to wide. Breeding is conducted mainly with no regard to body type. Only in few breeds body type is among major selection criteria. Among the narrow-bodied breeds, the greatest number of animals of the desired type was found in White Giants (78,0 % in total, 82,8 in the young, and 76,7 % in adults) and among the intermediate-type breeds, in Silvery rabbits (58,9, 61,5, and 55,9 %, respectively). No significant differences were found in wide-bodied breeds. The proportions of the desired type in the Californian breed were 40,0 in total, 33,4 in the young, and 55,9 % in adults and in the New Zealand White, 41,4, 40,8, and 42,0 %.